2015
DOI: 10.1111/add.12996
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation of reactivity to ecological momentary assessment frequency among adults trying to quit smoking

Abstract: Aims Ecological Momentary Assessment (EMA) captures real-time reports in subjects’ natural environments. This experiment manipulated EMA frequency to estimate effects on abstinence and peri-cessation subjective experiences. Design In this randomized trial, subjects had an equal chance of being assigned to low-frequency (once) or high-frequency (6 times) daily EMA for 4 weeks (1 week pre- and 3 weeks post-cessation). Participants completed 6 office visits over 5 weeks and 6- and 12-week follow-up telephone in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
63
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 35 publications
8
63
0
Order By: Relevance
“…The prompt signaled participants to answer several self-report items and complete a brief momentary impulsiveness assessment, described below. We chose to use random EMA assessment only rather than ask participants to prompt reports of events following temptations or smoking because, unlike prior studies that examined only the first lapse post-quit (e.g., Shiffman et al, 1996), we wanted to assess smoking and temptations occurring over several weeks post-quit and aimed to reduce participant burden and possible assessment reactivity over time (McCarthy et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…The prompt signaled participants to answer several self-report items and complete a brief momentary impulsiveness assessment, described below. We chose to use random EMA assessment only rather than ask participants to prompt reports of events following temptations or smoking because, unlike prior studies that examined only the first lapse post-quit (e.g., Shiffman et al, 1996), we wanted to assess smoking and temptations occurring over several weeks post-quit and aimed to reduce participant burden and possible assessment reactivity over time (McCarthy et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…However, there are studies that have examined EMA reactivity within smoking cessation trials and have found minimal to no behavioral changes due to EMA (Shiffman et al, 2002; Rowan et al, 2007). In a recent study designed to test EMA reactivity within a smoking cessation trial using randomly assigned EMA frequency conditions, researchers found that EMA frequency was unrelated to cessation or prolonged abstinence (McCarthy et al, 2015). Given these findings, it is reasonable to assume that EMA is an appropriate measurement method, particularly for smoking cessation clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, findings from our study add to the ongoing discussion about assessment reactivity within EMA research (20,21,23). Participants from our study anticipated that repeated assessment of mood and behavior could change their drug-related behavior.…”
Section: Discussionmentioning
confidence: 59%
“…Some researchers pose that "assessment reactivity," or shifts in behavior over time as it is intensely monitored during EMA studies, may be a benefit of this methodology (5). However, the studies that have explored assessment reactivity within the field of EMA have produced mixed results (20)(21)(22)(23). For example, in the field of alcohol abuse research, Epstein et al showed that assessment of alcohol use, mental health and affect via EMA triggers reduction in drinking pre-treatment among alcohol-dependent women (20), but Hufford et al's study of alcohol-abusing college students did not show changes in drinking frequency during EMA recording, relative to pre-EMA levels (22).…”
Section: Introductionmentioning
confidence: 99%